2020
DOI: 10.1101/2020.03.19.999078
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Meta-analysis suggests the microbiome responds to Evolve and Resequence experiments inDrosophila melanogaster

Abstract: Experimental evolution has a long history of uncovering fundamental insights into evolutionary processes but has largely neglected one underappreciated component-the microbiome. As eukaryotic hosts evolve, the microbiome may also evolve in response. However, the microbial contribution to host evolution remains poorly understood. Here, we analyzed the metagenomes from 10 E&R experiments in Drosophila melanogaster to determine how the microbiome changes in response to host selection. Bacterial diversity was sign… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
0
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 96 publications
(129 reference statements)
1
0
0
1
Order By: Relevance
“…However, missing from this framework is the role of the microbiome. In a survey of ten E&R experiments, the microbiome also frequently responded to experimental evolution, particularly in traits associated with metabolism [80]. Taken together, our data here also highlight how the microbiome may contribute to host adaptation, previously unseen by focusing only on the Drosophila genome.…”
Section: Conclusion and Research Prioritiessupporting
confidence: 52%
“…However, missing from this framework is the role of the microbiome. In a survey of ten E&R experiments, the microbiome also frequently responded to experimental evolution, particularly in traits associated with metabolism [80]. Taken together, our data here also highlight how the microbiome may contribute to host adaptation, previously unseen by focusing only on the Drosophila genome.…”
Section: Conclusion and Research Prioritiessupporting
confidence: 52%
“…The authors detected large discrepancies in the measures of alpha and beta diversity as well as in the relatve abundances of several bacteria taxa in the microbiome between Wolbachiainfected fy samples (mean abundance of 98.8% for Wolbachia sequences) and non-infected. This and other work has shown that in some cases removing the Wolbachia-associated reads from the analyses could also have major impacts in the interpretaton of the study results which may be especially relevant when comparing infected samples versus non-infected (Henry & Ayroles, 2021;Wilches et al, 2021). We addressed the impact of removing Wolbachia reads in microbiota diversity and structure in M.…”
Section: Discussionmentioning
confidence: 99%
“…El interés de introducir el concepto hologenómico de evolución reside, por tanto, en explicar de manera adaptativa todos los procesos que ocurren dentro del microbioma, y que llevan al incremento de la eficacia biológica esperada -entendida como su reproducción-de la base genética que codifica rasgos beneficiosos para el hospedero, y del propio hospedero, siempre que este último tenga éxito en incentivar dichos efectos (Rudman et al, 2019;Roughgarden, 2020;Henry & Ayroles, 2020). Estos efectos quedarían sin explicación adaptativa de no aceptarse la tesis de que el holobionte/hologenoma es un interactor.…”
Section: Figuraunclassified